ISOLASI DAN IDENTIFIKASI PEKTIN DARI KULIT PISANG MAS (Musa acuminata Colla) - Panal Sitorus; Supartiningsih Supartiningsih; Jon Kenedy Marpaung; Bernadetta R. Munthe (Jurnal Farmanesia, 2020)
Pectin is one of the types of carbohydrate from polysacharide compound derivatives found in plan cell walls. pectin can be used in the viscosity, stability, texture and appearance of the food. The use of pectin in pharmacy is used for diarrhea, where pectin works as absordent in the intestine and also used as wound medicine as the hemostatic agent. The purpose of this research is utilize the mas banana peel as the source of pectin. This research was conducted by using the reflux extraction method using 1N hydrochloric acid as a solvent. Pectin isolation at pH 2, temperature 70-80-C for 60 minutes. The result of the precipitate is then added ethanol into the filtrate to precipitate the pectin and the final process is drying to obtain dry pectin which is 2.2975 gr. Dried pectin is obtained in the form of a fine powder, reddish brown in color and practically insoluble in ethanol. From the result of the identification that was carried out positive for the reaction with the addition of 96% ethanol and 2N NaOH, there was a gel which when added with 3N HCI and heated it formed brownish yellow lumps and had a distinctive odor. Physical specific characterization of pectin was also carried out, including moisture content (31.37%) and ash content (38.79%). Pure pectin standard for maximum moisture content of 12%, and maximum ash content of 10%. Pectin from mas banana (Musa acuminataColla) does not meet IPPA (International Pectin Producers Association) quality standards. Keywords: Banana peel, pectin, extraction, Reflux